Double Moral Hazard and Outcome-based Remuneration of Physicians - Udo Schneider (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
The discussion about health care systems focuses on the dynamics of expenditures and on the weak growth of the revenue base. In this discussion it is widely overseen that medical expenditures and supply of medical services crucially depend on the compensation of physician services. The paper analyses the implementation of an outcome-based payment system in the presence of asymmetric information. Two cases are studied in detail: first, the common situation of physician's moral hazard and second, a double moral hazard model. The choice of insurance and payment contracts then depends on the characteristics of asymmetric information.
Keywords: I11; I12; D82; 330; outcome-based remuneration; double moral hazard; health policy